Modeling The Effects of Mother’s Age at First Birth on Child Health at Birth - Tambi, Mbu Daniel (Asian Journal of Economic Modelling, 2014)
This study models the impact of mother’s age at first birth on child health at birth in Cameroon. The objectives are: (1) investigate the implication of mother’s age at first birth on child health at birth; (2) examine the impact of mother’s age groups on birth weight, and (3) suggest economic policies to ameliorate the mother’s age – child health relationship. We make used of the control function approach to determine the relationship between mother’s age at first birth and birth weight. The 2011 Cameroon demographic and health survey data is use to estimate our result in STATA 10.1. The result reveals that mother’s age at first birth is negatively correlating with birth weight. Evidences by age group suggest that rates of adverse perinatal outcome such as low birth weight and stillbirth are linked to maternal age 35–39 years old. Based on our results, we recommend that aspiring mothers should endeavour to give birth to their first child before 35 years while mother’s already advanced in age should follow closely their prenatal and medical services. This is a major step towards poverty alleviation due to low birth weight complications.